Project-Based Learning as an Innovative Approach to Improve Elementary Social Studies Learning Outcomes - Tangke, Fadlun Nirman; Nashrullah, Nashrullah; Herlina, Herlina; Muchdar, Muchdar; Wilade, Surahman (Papanda Publisher, 2025)
Traditional lecture-based instruction in Indonesian elementary Social Studies education often results in passive student participation and suboptimal learning outcomes. This study examined the effectiveness of Project-Based Learning (PjBL) as an alternative pedagogical approach to enhance student engagement and academic achievement in fourth-grade Social Studies instruction. A quasi-experimental study with nonequivalent control group design was conducted at SD Negeri 9 Palu, involving 26 fourth-grade students randomly assigned to experimental (n=13) and control (n=13) groups. The experimental group received eight weeks of PjBL instruction focusing on human body organ systems through collaborative investigations, while the control group received conventional lecture-based teaching. Data were collected using a validated 20-item multiple-choice achievement test administered as pretest and posttest. Statistical analyses included descriptive statistics, assumption testing, independent samples t-tests, and paired samples t-tests with significance set at α = 0.05. The experimental group achieved significantly higher posttest scores (M = 88.07, SD = 6.62) compared to the control group (M = 80.38, SD = 9.23), with a statistically significant difference (t = 2.416, p = 0.024) and large effect size (Cohen's d = 0.95). Both groups showed significant within-group improvements, but the experimental group demonstrated greater consistency in learning outcomes with substantially reduced variance (474.35 to 43.91). Project-Based Learning significantly enhances Social Studies learning outcomes and promotes more equitable educational experiences among fourth-grade students. The findings support the implementation of student-centered pedagogical approaches in Indonesian elementary education contexts. Future research should examine PjBL effectiveness across larger samples and extended intervention periods while exploring individual learner characteristics that may influence outcomes.